Career Construction Experiences of Syrian Refugee Women in Turkish Higher Education: Opportunities and Obstacles - Çirkin, Zeynep; Sakiz, Halis; Çuhadar, Pinar (Refuge, 2025)
This study explores the career construction and higher education opportunities and challenges faced by Syrian refugee women in Türkiye through semi-structured interviews with 40 women enrolled at a public university. Findings reveal significant challenges in career construction and higher education stemming from the intersectionality of gender and refugee status, including job market discrimination, increased housework and caregiving responsibilities, and moral concerns about independent women. The study also identifies opportunities for empowerment through women’s rights, autonomy, equality, and self-sufficiency. It contributes to refugee studies, higher education, and integration by acknowledging the transformative potential of education and employment for Syrian refugee women.